Pengaruh Pemberian Aromaterapi Lavender pada Penderita Hipertensi dengan Gangguan Rasa Nyaman - Indra Febriani; Faiza Yuniati; Sri Martini; Jawiyah Jawiyah; Peni Ana Sari (Jurnal Ilmiah Universitas Batanghari Jambi, 2022)
Hypertension is a condition of increased pressure that can cause various complications. This study aims to determine the effect of giving lavender aromatherapy to hypertensive clients with comfort disorders. This research uses a case study method with a nursing process approach. The study was conducted on March 25, 2022 to March 10, 2022. The number of respondents was 2 people with an intervention time of 4 days. The research was conducted in the working area of 23 Ilir Health Center Palembang. The results showed that after the intervention of giving lavender aromatherapy, there was a change in the pain scale from a pain scale of 5 to 1 in 2 clients. The intervention of giving lavender aromatherapy has an effect on reducing the comfort of hypertensive clients with headaches